Determination of fast neutron RBE using a fully mechanistic computational model. (February 2020) - Zabihi, Azam; Tello, John; Incerti, Sebastien; Francis, Ziad; Forozani, Ghasem; Semsarha, Farid; Moslehi, Amir; Bernal, Mario A.
Abstract: This work presents a model previously developed for estimating relative biological effectiveness (RBE) associated with high-LET particles. It is based on the combination of Monte Carlo simulations of particle interactions when traversing an atomic resolution DNA geometrical model. In addition, the model emulates the induction of lethal damage from the interaction of two sublethal lesions, taken as double-strand breaks. The Geant4-DNA package was used for simulations with liquid water as the transport medium. The RBE of neutron beams with energies ranging from 0.1 MeV up to 14 MeV was studied. The model succeeded in reproducing the general behavior of RBE as a function of neutron energy, including the RBE peak reported by experiments at approximately 0.4 MeV. Furthermore, the results of the model agree rather well with some experimental works. However, our results underestimate RBE for neutron energies above approximately 5 MeV due to the current limitations of Geant4-DNA for the tracking of heavy ions below 0.5 MeV/u. Highlights: A biophysical model based on the Dual Radiation Action Theory of Kellerer and Rossi is used for estimating RBE for fast neutrons. A whole cell DNA model with atomic resolution is irradiated with neutron beams. Linear and quadratic components of the dose-effect formula are reproduced. RBE consistent with experiments were obtained. The general behavior of RBE versus neutron energy was successfully reproduced.